An engineered anti-idiotypic antibody-derived killer peptide (KP) early activates swine inflammatory monocytes, CD3+CD16+ natural killer T cells and CD4+CD8α+ double positive CD8β+ cytotoxic T lymphocytes associated with TNF-α and IFN-γ secretion. (October 2020) - Ferrari, Luca; Martelli, Paolo; Saleri, Roberta; De Angelis, Elena; Ferrarini, Giulia; Cavalli, Valeria; Passeri, Benedetta; Bazzoli, Gianluca; Ogno, Giulia; Magliani, Walter; Borghetti, Paolo
Highlights: KP early induces pro-inflammatory CD172α+CD14 +high monocytes and CD3 + CD16 + NKT cells. KP triggers CD8α and CD8β expression on CTL and CD4 + CD8α + Th memory cells. KP induces two CD4 + CD8α + CTL subsets associated with increased TNF-α and IFN-γ secretion. KP boosts PRRSV-1- and PCV2b-specific IFN-γ SC reactivity and cross-reactivity. KP is promising as a Th1 response immunomodulator or vaccine adjuvant in pigs. Abstract: This study evaluated the early modulation of the phenotype and cytokine secretion in swine immune cells treated with an engineered killer peptide (KP) based on an anti-idiotypic antibody functionally mimicking a yeast killer toxin. The influence of KP on specific immunity was investigated using porcine reproductive and respiratory syndrome virus (PRRSV) and porcine circovirus type 2 (PCV2) as ex vivo antigens. Peripheral blood mononuclear cells (PBMC) from healthy pigs were stimulated with KP and with a scramble peptide for 20 min, 1, 4 and 20 h or kept unstimulated. The cells were analyzed using flow cytometry and ELISA. The same time-periods were used for KP pre-incubation/co-incubation to determine the effect on virus-recalled interferon-gamma (IFN-γ) secreting cell (SC) frequencies and single cell IFN-γ productivity using ELISPOT. KP induced an early dose-dependent shift to pro-inflammatory CD172α + CD14 +high monocytes and an increase of CD3 + CD16 + natural killer (NK) T cells. KP triggered CD8α and CD8β expression on classical CD4 − CD8αβ + cytotoxic T lymphocytes (CTL) and double positive (DP) CD4 + CD8α + Th memory cells (CD4 + CD8α +low CD8β +low ). A fraction of DP cells also expressed high levels of CD8α. The two identified DP CD4 + CD8α +high CD8β +low/+high CTL subsets were associated with tumor necrosis factor alpha (TNF-α) and IFN-γ secretion. KP markedly boosted the reactivity and cross-reactivity of PRRSV type-1- and PCV2b-specific IFN-γ SC. The results indicate the efficacy of KP in stimulating Th1-biased immunomodulation and support studies of KP as an immunomodulator or vaccine adjuvant.